2021
DOI: 10.1016/j.ijpharm.2021.120686
|View full text |Cite
|
Sign up to set email alerts
|

Nasal vaccination against SARS-CoV-2: Synergistic or alternative to intramuscular vaccines?

Abstract: It is striking that all marketed SARS-CoV-2 vaccines are developed for intramuscular administration designed to produce humoral and cell mediated immune responses, preventing viremia and the COVID-19 syndrome. They have a high degree of efficacy in humans (70-95%) depending on the type of vaccine. However, little protection is provided against viral replication and shedding in the upper airways due to the lack of a local sIgA immune response, indicating a risk of transmission of virus from vaccinated individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 118 publications
0
113
0
3
Order By: Relevance
“… Fasina and Lillehoj (2019) showed that CP infection could induce intestinal inflammation in broilers, which may be mediated by Threshold (Th) 2 and Th17 cells. sIgA antibody, as the first line of antigen-specific immune defense, protects the mucosal surface from environmental pathogens and antigens by combining with bacterial antigens ( Tiboni et al, 2021 ). We also found that BST treatment upregulated the expression levels of sIgA in the jejunum.…”
Section: Discussionmentioning
confidence: 99%
“… Fasina and Lillehoj (2019) showed that CP infection could induce intestinal inflammation in broilers, which may be mediated by Threshold (Th) 2 and Th17 cells. sIgA antibody, as the first line of antigen-specific immune defense, protects the mucosal surface from environmental pathogens and antigens by combining with bacterial antigens ( Tiboni et al, 2021 ). We also found that BST treatment upregulated the expression levels of sIgA in the jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…The IM-administered EUA vaccines currently in use offer very satisfactory levels of protection but their ability to prevent asymptomatic transmission is still unclear (reviewed by Tiboni et al, 2021). Vaccines delivered intranasally stand a higher chance of eliciting local mucosal immunity preventing not only systemic infection but also local replication and shedding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a significant difference in the viral RNA and viral load in the oropharyngeal swabs for IN vaccinated compared to control animals, while no difference in the amount of viral RNA and infectious virus was noted for IM vaccinated animals as compared to the control. No viral RNA or infectious virus was detected in lung tissue from IN vaccinated animals [54,55]. IN vaccination in rhesus macaques by means of a mucosal atomization device was performed.…”
Section: Chadox1-smentioning
confidence: 99%